Interpreting quantum efficiency for energy and environmental applications of photo-catalytic materials. (September 2021) - Kubacka, Anna; Barba-Nieto, Irene; Caudillo-Flores, Uriel; Fernández-García, Marcos
Graphical abstract: Abstract : The use of efficiency observables to measure activity is of critical importance in order to progress in the quantitative assessment of the functional properties of photo-catalysts in energy and environmental related applications. In this quest, the analysis of the experimental/computational procedures to obtain efficiency observables and the associated unsolved problems are reviewed. Particularly, the contribution analyzes the current efforts to fully interpret the effect(s) of the light-matter interaction as well as the dimensionality of the observable.